Development of new osmotic tensiometers for high soil suction measurement - Liu, Hengshuo (Nanyang Technological University, 2023)
Soil can be divided into unsaturated soil and saturated soil according to the position of the groundwater table. The soil above the groundwater table is defined as unsaturated soil and it has four components including air, water, air-water interface, and solid soil particles. In unsaturated soil, its soil suction can significantly influence the hydromechanical behavior and engineering properties of the soil. Soil suction comprises two parts: matric suction and osmotic suction. Matric suction is caused by the capillarity of soil particles on pore-water and its value is defined as the difference between the pore-air pressure and the pore-water pressure, while osmotic suction relates to the dissolved salts in the pore-water of the soil. Conventional water-filled tensiometers are widely used for direct measurement of matric suction under atmospheric conditions. The conventional tensiometer usually consists of a ceramic disk, a chamber filled with water, and a pressure transducer. The measuring range of the conventional tensiometer is up to 90 kPa due to the cavitation problem. Compared with conventional tensiometers, polymer-filled osmotic tensiometers (OTs) can measure a higher matric suction by increasing the osmotic pressure of the water inside the tensiometer. Similar to the suction measurement process using the conventional tensiometer, when placing the OT in contact with the soil for soil suction measurement, the suction of the soil will induce a drop in the osmotic pressure of the water in the polymer chamber of the OT and this drop is the value of matric suction of the soil. The measuring range of an OT is equal to the maximum water pressure of the OT during pressure observation. However, the long-term water pressure decay of OT caused a gradual decrease in its measuring range. All previous research used commercial polymers in developing OT and the mechanism of water pressure decay of OT was not found. In this research, the mechanism of water pressure decay in OT was first studied by correlating to polymer theories and appropriate super-water absorbent polymers were synthesized to develop new OTs with a constant measuring range. The good performance of the developed OTs in soil suction measurement was evaluated using the undisturbed residual soil specimens. The temperature effect on OT was also studied based on polymer theories. Commercial crosslinked poly(acrylamide-co-acrylic acid) potassium salt (PAM-co-PAAK) was used for the preparation of OTs to explore the mechanism of water pressure decay of OTs. The maximum water pressure in the OT (i.e., the measuring range of the OT) versus the volume fraction of polymer filled in the OT was described based on the Flory-Huggins polymer theories and validated using the WP4C dewpoint potentiometer. The long-term observation of pressure variation of OTs indicates that the pressure decay of OT was mainly caused by the stress relaxation of the polymer hydrogels, and the standard linear solid (SLS) rheological model can fit the decay data properly. The ultraviolet-visible spectrophotometry demonstrated that there was no increase in polymer leakage during the period of pressure decay of OTs. As a result, the pressure decay of OT was proved not caused by polymer leakage. Referring to the mechanism of water pressure decay in OT, new OTs were developed using synthesized polymers. Polymers including polyacrylamide (PAM) and sodium polyacrylate (NaPA) with different degrees of cross-linking were synthesized by UV polymerization. Long-term pressure variations of OTs show that PAM-filled OTs have a faster stress relaxation behavior than NaPA-filled OTs and thus can keep constant pressure (i.e. constant measuring range) for a long time. However, the measuring range of PAM-filled OTs is lower than that of NaPA-filled OTs when the same mass of polymer was filled in OT. The residual soil specimens with controlled matric suction were used to evaluate the performance of OTs in matric suction measurement. The results demonstrated that OTs can measure matric suction with fast response and high accuracy. Three OTs with different measuring ranges were prepared to study the temperature effect on the pressure variation of OT. The pressure decay of OT was proved insignificant to the accuracy of soil suction measurement if the measurement can be conducted in a short time (e.g., less than one hour). Based on Flory-Huggins polymer theories, an appropriate temperature calibration equation was proposed to eliminate the temperature effect on soil suction measurement using OT. The developed OT was also used to determine the SWCC of a residual soil over the full range by combining it with a pressure plate and WP4C dewpoint potentiometer. Comparison of the experimental data from the pressure plate, OT, and WP4C dewpoint potentiometer proves that the OT had good performance in the determination of SWCC, especially for the transition zone (i.e., 10 – 1500 kPa suction range), by providing more data points to define the SWCC in a shorter period. The usage of OT will improve the accuracy and the speed of high soil suction measurement, thus shortening the time required for the determination of SWCC. The results of this research show that the developed OT could be considered as a new and reliable instrument in high matric suction measurement and thus contribute to the research and application of unsaturated soil mechanics.